Selection of control, randomization, blinding, and allocation concealment - Amrita Sil; Piyush Kumar; Rajesh Kumar; Nilay Kanti Das (Wolters Kluwer Medknow Publications, 2019)
Clinical trials looking at which treatment is better must have certain checks in place. Appropriate "control" selection while comparing the investigating agent to the "control group is essential to rule out selection bias. Randomization is another step to minimize variability or "confounders." By randomization, research participants have an equal chance of being selected into any treatment group of the study, generating comparable intervention groups, thereby distributing the confounders. A trial can be "open labeled" or "blinded." By the process of blinding, we make the participant and/or assessing physician unaware of the treatment he/she is going to receive. Thus, the element of bias which can creep in owing to personal preference or subjective component to the assessment of outcome can be eliminated. Concealment of allocation is done as the participant enters the trial. Concealment secures randomization and prevents "selection bias".